02 Successful withdrawal of 3, 4—Diaminopyridine: a report on six patients with Lambert Eaton Myasthenic Syndrome. Issue 3 (15th February 2011) - Punter, M N M; Zermansky, A; Ramdass, R; MacDonagh, R J; Marshall, A G; Sussman, J D; Roberts, M E
Abstract : The treatment cost of Lambert Eaton Myasthenic Syndrome with 3, 4-Diaminopyridine has recently increased markedly, renewing interest in other therapies. We report our first six patients in whom we have attempted to withdraw 3, 4-DAP. Four patients have each been followed up over 5 years with no evidence of underlying malignancy. One patient had small cell lung cancer now in remission and 1 patient has been followed up for 1 year without malignancy. The paraneoplastic LEMS patient tolerated abrupt cessation of 3, 4-DAP without clinical or neurophysiological deterioration or additional therapy. Two patients with autoimmune LEMS failed to tolerate abrupt cessation, requiring pyridostigmine and prednisolone to remain minimally symptomatic off 3, 4-DAP. One autoimmune patient treated with prednisolone tolerated a gradual withdrawal of 3, 4-DAP with the addition of pyridostigmine. One autoimmune patient tolerated a 60% reduction of 3, 4-DAP with concurrent mycophenolate, aiming for complete cessation. A single autoimmune patient failed to tolerate a reduction in 3, 4-DAP and is currently initiating immunosuppression. Our patient with treated lung malignancy was the only one to successfully withdraw all therapy without symptom recurrence. The other patients have required immunosuppression and pyridostigmine. These differences may reflect the underlying disease processes. We conclude that in these financially straitened times LEMS can be effectively managed without the use of 3, 4-DAP.